Cost of Respiratory Syncytial Virus-Associated Acute Lower Respiratory Infection Management in Young Children at the Regional and Global Level: A Systematic Review and Meta-Analysis. (30th March 2020) - Zhang, Shanshan; Akmar, Lily Zainal; Bailey, Freddie; Rath, Barbara A; Alchikh, Maren; Schweiger, Brunhilde; Lucero, Marilla G; Nillos, Leilani T; Kyaw, Moe H; Kieffer, Alexia; Tong, Sabine; Campbell, Harry; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory infection (ALRI) in young children aged <5 years. Methods: We aimed to identify the global inpatient and outpatient cost of management of RSV-ALRI in young children to assist health policy makers in making decisions related to resource allocation for interventions to reduce severe morbidity and mortality from RSV in this age group. We searched 3 electronic databases including Global Health, Medline, and EMBASE for studies reporting cost data on RSV management in children under 60 months from 2000 to 2017. Unpublished data on the management cost of RSV episodes were collected through collaboration with an international working group (RSV GEN) and claim databases. Results: We identified 41 studies reporting data from year 1987 to 2017, mainly from Europe, North America, and Australia, covering the management of a total of 365 828 RSV disease episodes. The average cost per episode was €3452 (95% confidence interval [CI], 3265–3639) and €299 (95% CI, 295–303) for inpatient and outpatient management without follow-up, and it increased to €8591(95% CI, 8489–8692) and €2191 (95% CI, 2190–2192), respectively, with follow-up to 2 years after the initial event. Conclusions: Known risk factors (early and late preterm birth, congenital heart disease, chronic lung disease, intensive care unit admission, and ventilator use) were associated with €4160 (95% CI, 3237–5082) increased cost of hospitalization. The global cost of inpatient and outpatient RSV ALRI management in young children in 2017 was estimated to be approximately €4.82 billion (95% CI, 3.47–7.93), 65% of these in developing countries and 55% of global costs accounted for by hospitalization. We have demonstrated that RSV imposed a substantial economic burden on health systems, governments, and the society.